The Influence of BOPO, Profit Sharing Financing, NPF, and FDR on UUS Profitability - Triyuwono, Iwan; Windayani, Erilla (Basic and Applied Accounting Research Journal, 2024)
This study aims to examine the effect of Operational Costs to Operating Income (BOPO), profit sharing financing, Non Performing Finance (NPF), and Financing to Deposit Ratio (FDR) on the profitability of Sharia Business Units as measured by Return On Assets (ROA). This study applies quantitative association method, analyzing data by multiple linear regression processed by SPSS 26. The population includes all sharia business units in Indonesia as recorded by the Sharia Banking Statistics (SPS) for December 2023, from which the samples of 15 sharia business units are selected through purposive sampling, involving data of the sharia business units’ quarterly published reports in December for the 2018-2022 period, obtained from the official websites of respective Sharia Business Units. The results of the study exhibit that profit sharing financing and NPF have a negative and insignificant effect on profitability; BOPO has a negative and significant effect on profitability; and FDR has a positive and significant effect on profitability.